Pilot Study of Videos to Deliver Mindfulness-Based Art Therapy for Adults With Multiple Sclerosis. Issue 6 (December 2020) - Newland, Pamela; Miller, Rebecca; Bettencourt, B. Ann; Hendricks-Ferguson, Verna
Abstract : ABSTRACT: BACKGROUND: Mindfulness-based art therapy (MBAT) has been shown to provide a strategy for adults with multiple sclerosis (MS) to self-manage their symptoms. There is a need for the use of an MBAT intervention that can be delivered in any setting for adults with MS. The purpose of this pilot feasibility study was to test the feasibility and acceptability of an MBAT intervention delivered via videoconference. METHODS: We developed an MBAT intervention to be delivered by videoconference to adults with MS recruited from an academic center registry. We also conducted phone interviews to collect acceptability data. RESULTS: Most of the participants (n = 5) were very positive about the MBAT video sessions and stated content as clear and easy to follow and understand. The time and delivering method were acceptable. CONCLUSION: Mindfulness-based art therapy sessions delivered through videoconference are acceptable and feasible for adults with MS. Abstract : Supplemental digital content is available in the text.